2019
DOI: 10.31788/rjc.2019.1235215
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SENNA (Senna alexandrina Mill.) AND POMEGRANATE (Punica granatum L.) LEAVES EXTRACTS AND ITS FRACTIONS ON PRO-INFLAMMATORY CYTOKINES OF THE OBESE ZEBRAFISH (Danio rerio)

Abstract: Obesity-associated with several chronic diseases. Based on this condition, natural products use should be considered as an alternative treatment. The objectives of this research are to evaluate the effect of senna (Senna alexandrina Mill.) and pomegranate (Punica granatum L.) leaves extracts and its fractions on pro-inflammatory cytokines suppression of the obese zebrafish. Methods: acclimatization period was performed for two weeks. All zebrafish was given by standard diet intake. Post acclimatization, zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Kombinasi kayu secang, kayu manis, dan daun Ruella tersebut memberikan efek antioksidan dan antidiabetes dengan mekanisme penghambatan alpha glucosidase dan penangkapan radikal bebas (Rosmalena et al, 2022). Kombinasi daun jati cina dan delima dilaporkan memiliki aktivitas antidiabetes, antioksidan, dan antiobesitas (Yuniarto et al, 2018).…”
Section: Hasil Penelitianunclassified
“…Kombinasi kayu secang, kayu manis, dan daun Ruella tersebut memberikan efek antioksidan dan antidiabetes dengan mekanisme penghambatan alpha glucosidase dan penangkapan radikal bebas (Rosmalena et al, 2022). Kombinasi daun jati cina dan delima dilaporkan memiliki aktivitas antidiabetes, antioksidan, dan antiobesitas (Yuniarto et al, 2018).…”
Section: Hasil Penelitianunclassified
“…Yellow pea, aphaca, wild pea, Indian flower [214] Europe, Asia, Africa [214] Flower [214] na Seeds contain toxic amino acids [133] Senna, cassia, sen, cassia angustifolia [53,214] Egypt [214,215] Leaf, fruit, flower [53,214,216] Ericaceae Rhododendro n simsii Planch.…”
Section: Euphorbiace Aementioning
confidence: 99%
“…Activity: laxative, antipyretic, purgative, diuretic, stomach[53,215,216] Arial part: infusion Fabaceae Senna corymbosa (Lam.) H. S.Irwin & BarnebyButtercup bush, Argentine Senna, sena del campo, rama negra, mata negra[20,217,218] South America[20,217] Flower na Glycosides (anthraquinone glycosides, naphthoquinone), Activity: laxative, purgative, antidiabetic, hepatoprotective, antimalarial, antipyretic, antiasthmatic, antiviral, and antibacterial[20,217,218] Arial part: infusion na Alkaloids (grayanotoxane (pollen, nectar, and leaves)), phenols (flavonoids), and benzoic acid derivatives[207] Treatment: gastrointestinal disorders, asthma, arthritis, skin diseases, cough, resolving sore toxin, amenorrhea, expectorant, and bronchitis[207] Activity: anti-inflammatory, anti-herpes, antioxidant, antiviral, hepatoprotective, and sedative[207,208] Arialpart: infusion Euphorbiaceae Euphorbia milii Des Moul.…”
mentioning
confidence: 99%
“…Additionally, Vroegrijk et al [35] demonstrated that PG seed oil treatment can improve peripheral insulin sensitivity in C57Bl/J6 mice. Furthermore, α-glucosidase and α-amylase assays showed the capacity of PG leaf extract to inhibit these enzymes, and there were also reports of enzymatic inhibition of pancreatic lipase [80]. However, there have also been contradictory findings regarding the anti-hyperglycemic potential of PG [40,61].…”
Section: Type 2 Diabetes and Pomegranate Consumptionmentioning
confidence: 99%